Academic stress and self-esteem in students of a Public Educational Institution in Trujillo, 2026 - Katheryn Nayeli Rojas-Salazar; Helaman Ernesto Guevara-Alcalde; Jose Luis Olivera-Orihuela; Andrea Nicole Cumpa-Sandoval (TUMI Health Sciences Research, 2026)
Background: Academic stress represents an important challenge during adolescence because increasing school demands may affect students’ psychological well-being and adaptation. Self-esteem may play a relevant role in how adolescents perceive and respond to these demands. Objective: To determine the association between academic stress and self-esteem among students at a public educational institution in Trujillo, Peru, in 2026. Methods: An observational, analytical, cross-sectional study with a quantitative approach was conducted in 151 adolescents. Academic stress and self-esteem were assessed using structured questionnaires with evidence of content validity and adequate internal consistency. Categorical variables were summarized using frequencies and percentages, and associations were evaluated using Pearson’s chi-square test, with statistical significance set at p < 0.05. Results: Academic stress was predominantly moderate (54.3%), followed by high (35.1%) and low (10.6%) levels. Self-esteem was mainly moderate (75.5%), followed by high (23.8%) and low (0.7%) levels. No statistically significant association was found between overall academic stress and self-esteem (p = 0.218). However, the self-esteem dimension of power was associated with overall academic stress (p = 0.010), while task overload (p = 0.002) and concern about grades (p = 0.043) were associated with overall self-esteem. Conclusions: Overall academic stress and self-esteem were not significantly associated; however, specific dimensions of both constructs showed significant associations, suggesting that their relationship may be better understood through dimensional rather than exclusively global assessment.